Computer-based learning for the enhancement of breastfeeding training for South African undergraduate dietetic students - Du Plessis, Lisanne (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MNutr (Interdisciplinary Health Sciences. Human Nutrition))--University of Stellenbosch, 2007.